“I think we don't have a really good way to talk about intelligibility”: An interview with John Levis - Germán Zárate-Sández; Alison Roberto Gonçalves (Ilha do Desterro)
In his influential paper, John Levis (2005) argued that pronunciation teaching is influenced by two conflicting ideologies: the nativeness principle, which suggests learners should strive to sound like native speakers, and the intelligibility principle, which emphasizes that learners should focus on being intelligible and developing speech patterns that are contextually appropriate. These two principles often clash, creating a conflict between teachers' pedagogical practices and their theoretical knowledge. Almost two decades after its publication, Levis (2005) continues to be a significant contribution for researchers when reflecting on the role of pronunciation in Applied Linguistics. In light of this, we decided to interview John Levis to celebrate his impressive career as a researcher and professor, and to reflect on this ongoing issue in teacher education. In this interview, Levis discusses his initial trajectory as a researcher and shares his ideas about current issues in pronunciation research.